Novel method suitable for palladium-free chemical copper plating on surface of Al2O3 ceramic electronic substrate
Through the redox reaction of the Al2O3 ceramic substrate's own temperature catalytic activation liquid, palladium-free electroless copper plating is realized, which solves the problems of high cost, poor stability and difficulty in large-scale production in the existing technology, and achieves low-cost, stable and uniform plating. The effect of the copper layer.
Patent Information
- Application Number
- CN202411445300.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing Al2O3 ceramic electronic substrate surface electroless copper plating method has high cost, poor stability, and is difficult to produce on a large scale.
The Al2O3 ceramic substrate's own temperature catalyzes the oxidation-reduction reaction of the activation liquid to achieve palladium-free electroless copper plating. Specific steps include heat-treating the Al2O3 ceramic substrate to a specified temperature, spraying a mixed solution of copper sulfate and vitamin C for activation, and then immersing it in the plating solution for electroless copper plating reaction.
A low-cost, stable, and large-scale palladium-free electroless copper plating process has been achieved. The copper plating layer is evenly distributed, has high production efficiency, is economical and environmentally friendly, and the process is simple and easy to control, making it easy to put into large-scale production.
Smart Images

Figure CN119332233A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of surface modification and metallization of non-metallic materials, and particularly relates to a new method for palladium-free chemical copper plating on the surface of an Al2O3 ceramic electronic substrate. Background Art
[0002] With the advancement of science and technology and the in-depth development of modern engineering technology, various electronic information products have penetrated into various fields of our lives, such as aerospace, communication technology, precision equipment, and new energy technology. In these fields, electronic substrates, as key components for carrying electronic components and realizing circuit connections, are gradually developing towards high-frequency, high-speed, and high-density integration. This trend has put forward more stringent requirements on the electrical, thermal, and mechanical properties of electronic substrates.
[0003] Al2O3 ceramic electronic substrates show their unique advantages among many electronic substrate materials due to their excellent electrical insulation properties, chemical stability and thermal stability. However, due to their non-metallic properties, Al2O3 ceramic substrates must be metallized before they can be used. At present, common metallization technologies include magnetron sputtering, screen printing and chemical plating. Among them, chemical plating technology has been widely used in industry due to its low requirements for production equipment, conditions and operating precision, as well as its advantages of not being restricted by substrate material and shape.
[0004] However, for the metallization treatment of Al2O3 ceramic substrates, it is usually necessary to use precious metals such as palladium for surface activation. The development of palladium activation technology has gone through stages such as sensitization-activation two-step method, sensitization-activation one-step method (also known as colloidal palladium activation method) and ion palladium activation method. Although the sensitization-activation two-step method is mature, its operation steps are cumbersome and it is difficult to achieve large-scale production. The colloidal palladium activation method simplifies the operation process, but its activation solution has poor stability and is prone to coagulation. The ion palladium activation method effectively improves the stability and service life of the activation solution by using ionic palladium solution. Although palladium activation technology is quite mature, the high cost is still an insurmountable difficulty, limiting its large-scale application in more fields.
[0005] To address this problem, this study proposed a new method for electroless copper plating on the surface of Al2O3 ceramic electronic substrates that does not require palladium activation. This method uses the temperature of the Al2O3 ceramic substrate to catalyze the activation liquid to undergo a redox reaction, causing the surface of the Al2O3 ceramic substrate to be evenly covered with copper particles, which then serve as the catalytic center for subsequent electroless copper plating, achieving a low-cost, stable, and large-scale palladium-free electroless copper plating process, providing a new idea for solving the problems existing in the existing technology. Summary of the invention
[0006] The present invention aims to solve the defects of the existing Al2O3 ceramic electronic substrate surface chemical copper plating method, such as high cost, poor stability, and difficulty in large-scale production, and provides a new palladium-free chemical copper plating method for the surface of Al2O3 ceramic electronic substrate activated by copper ions.
[0007] The present invention solves the above technical problems through the following technical solutions:
[0008] The present invention provides a palladium-free chemical copper plating method applicable to the surface of an Al2O3 ceramic electronic substrate, comprising the following steps:
[0009] Heat treating the Al2O3 ceramic substrate to a specified temperature;
[0010] The activation solution is uniformly sprayed on the Al2O3 ceramic substrate at a specified temperature for activation, wherein the activation solution is a mixed solution of copper sulfate and vitamin C;
[0011] The activated Al2O3 ceramic substrate is immersed in a plating solution to perform a chemical copper plating reaction.
[0012] Preferably, the heat treatment is carried out in a muffle furnace, heated to 100° C.-600° C., and kept warm for 1 min-10 min.
[0013] Preferably, the molar ratio of copper sulfate to vitamin C is 1:1-1:6;
[0014] And / or, the device used for the activation is a modified spray pot with a volume of 0.5L-5L;
[0015] And / or, the activation operation occurs within 1s-100s after the Al2O3 ceramic substrate has finished heat treatment;
[0016] And / or, the activation time is 5s-50s;
[0017] And / or, the activated Al2O3 ceramic substrate is rinsed with deionized water for 1s-20s and dried.
[0018] Preferably, the plating solution is prepared as follows: copper sulfate, soluble malate, sodium citrate, sodium hydroxide, 37% formaldehyde aqueous solution by mass, sodium n-octyl sulfate and o-phenanthroline are added into deionized water and mixed and dissolved.
[0019] Preferably, the amount of copper sulfate relative to deionized water is 6-26 g / L;
[0020] And / or, the amount of the soluble malate relative to deionized water is 4-24 g / L;
[0021] And / or, the amount of sodium citrate relative to deionized water is 5-25 g / L;
[0022] And / or, the amount of sodium hydroxide used relative to deionized water is 5-25 g / L;
[0023] And / or, the dosage of the formaldehyde aqueous solution relative to deionized water is 5-50 mL / L;
[0024] And / or, the amount of sodium n-octyl sulfate relative to deionized water is 0.005-0.05 g / L;
[0025] And / or, the amount of o-phenanthroline used relative to deionized water is 0.005-0.05 g / L.
[0026] Preferably, the reaction temperature of the chemical copper plating reaction is 20° C.-70° C.; and / or the reaction time of the chemical copper plating reaction is 10-60 min.
[0027] Preferably, the method further comprises: before the heat treatment, ultrasonically cleaning the Al2O3 ceramic substrate to degrease it, and then roughening it in a roughening solution; and / or, the Al2O3 ceramic substrate has an Al2O3 content of 90%-99%.
[0028] Preferably, the ultrasonic cleaning is first performed once with soap solution and then performed twice with deionized water.
[0029] Preferably, the time for the first ultrasonic cleaning is 10-30 min; the time for the second ultrasonic cleaning is 1-10 min.
[0030] Preferably, the roughening liquid comprises 2%-20% hydrofluoric acid and 0.5%-5% sulfuric acid, and the roughening conditions are roughening at a temperature of 50° C.-100° C. for 0.5 h-5 h; and / or, ultrasonic cleaning with deionized water for 1-10 min after roughening.
[0031] The reagents and raw materials used in the present invention are commercially available.
[0032] The positive and progressive effect of the present invention is that the present invention uses a muffle furnace to heat the Al2O3 ceramic substrate to an appropriate temperature and keeps it warm for an appropriate time, and then uses the temperature of the Al2O3 ceramic substrate itself to catalyze the activation liquid sprayed evenly on the Al2O3 ceramic substrate to undergo an oxidation-reduction reaction, so that the surface of the Al2O3 ceramic substrate is covered with copper, and then serves as a catalytic center for subsequent chemical copper plating. The present invention overcomes the shortcomings of the previous Al2O3 ceramic electronic substrate palladium activation process, and the copper-plated layer is evenly distributed, has high production efficiency, is economical and environmentally friendly, and has a simple and easy-to-control process, which is convenient for large-scale production and has huge potential application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1This is a comparison of the surface morphology of copper before and after activation in Example 1;
[0034] Figure 2 It is a comparison diagram of the surface morphology of comparative example 1 and embodiment 1. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0036] Example 1
[0037] (1) Degreasing: The Al2O3 ceramic substrate with an aluminum oxide content of 97% was immersed in soapy water and ultrasonically cleaned for 15 min, then ultrasonically cleaned with deionized water for 5 min, and then taken out and dried for later use.
[0038] (2) Roughening: The Al2O3 ceramic substrate obtained in step (1) was placed in a roughening solution containing 10% hydrofluoric acid and 2% sulfuric acid at a constant temperature of 70°C for 1 hour, then ultrasonically cleaned with deionized water for 5 minutes, and taken out and dried for later use.
[0039] (3) Heat treatment: The Al2O3 ceramic substrate obtained in step (2) is placed in a muffle furnace and kept at 400°C for 3 min.
[0040] (4) Activation: Place the prepared copper sulfate and vitamin C activation solution in a molar ratio of 1:2 into a modified spray bottle with a volume of 2 L, take out the Al2O3 ceramic substrate just treated in step (3) from the muffle furnace, and activate it within 20 seconds of taking it out using the modified spray bottle containing the activation solution. The activation time is 10 seconds. After the activation is completed, rinse it with deionized water for 20 seconds, and then dry it for use.
[0041] (5) Preparation of plating solution: 6 g of soluble malate, 9 g of sodium citrate and 8 g of sodium hydroxide were weighed and added into a 1 L beaker. Deionized water was added and stirred to completely dissolve. Then, a mixture of 9 g of copper sulfate and 8 mL of a 37% formaldehyde aqueous solution was slowly added under stirring. Precipitation was initially generated. As stirring occurred, the precipitate gradually dissolved. The solution was then filtered. After filtration, it was poured into a 1 L beaker. 0.02 g of sodium octyl sulfate and 0.004 g of o-phenanthroline were then added. Deionized water was then added to make the beaker solution reach 500 mL to obtain a plating solution.
[0042] (6) Copper plating: The Al2O3 ceramic substrate obtained by the treatment in step (4) is immersed in the plating solution prepared in step (5), and stirred at 40°C for 40 minutes to complete the surface chemical copper plating. The coating bonding strength is tested by the 100-grid method, and the grade is 5B. The square resistance is tested by the four-probe method, and the square resistance is 20mΩ / □.
[0043] Example 2
[0044] (1) Degreasing: The Al2O3 ceramic substrate with an aluminum oxide content of 97% was immersed in soapy water and ultrasonically cleaned for 15 min, then ultrasonically cleaned with deionized water for 5 min, and then taken out and dried for later use.
[0045] (2) Roughening: The Al2O3 ceramic substrate obtained in step (1) was placed in a roughening solution containing 10% hydrofluoric acid and 2% sulfuric acid at a constant temperature of 70°C for 1 hour, then ultrasonically cleaned with deionized water for 5 minutes, and taken out and dried for later use.
[0046] (3) Heat treatment: The Al2O3 ceramic substrate obtained in step (2) was placed in a muffle furnace and kept at 400°C for 4 min.
[0047] (4) Copper ion activation: Place a prepared copper sulfate and vitamin C activation solution with a molar ratio of 1:3 into a modified spray bottle with a volume of 2 L. Take out the Al2O3 ceramic substrate just treated in step (3) from the muffle furnace and activate it within 20 seconds using the modified spray bottle containing the activation solution. The activation time is 10 seconds. After the activation is completed, rinse with deionized water for 20 seconds and then dry for use.
[0048] (5) Preparation of plating solution: 6 g of soluble malate, 9 g of sodium citrate and 8 g of sodium hydroxide were weighed and added into a 1 L beaker. Deionized water was added and stirred to completely dissolve. Then, a mixture of 9 g of copper sulfate and 8 mL of a 37% formaldehyde aqueous solution was slowly added under stirring. Precipitation was initially generated. As stirring occurred, the precipitate gradually dissolved. The solution was then filtered. After filtration, it was poured into a 1 L beaker. 0.02 g of sodium octyl sulfate and 0.004 g of o-phenanthroline were then added. Deionized water was then added to make the beaker solution reach 500 mL to obtain a plating solution.
[0049] (6) Copper plating: The Al2O3 ceramic substrate obtained by the treatment in step (4) is immersed in the plating solution prepared in step (5), and stirred at 40°C for 40 minutes to complete the surface chemical copper plating. The coating bonding strength is tested by the 100-grid method, and the grade is 5B. The square resistance is tested by the four-probe method, and the square resistance is 26mΩ / □.
[0050] Example 3
[0051] (1) Degreasing: The Al2O3 ceramic substrate with an aluminum oxide content of 97% was immersed in soapy water and ultrasonically cleaned for 15 min, then ultrasonically cleaned with deionized water for 5 min, and then taken out and dried for later use.
[0052] (2) Roughening: The Al2O3 ceramic substrate obtained in step (1) was placed in a roughening solution containing 10% hydrofluoric acid and 2% sulfuric acid at a constant temperature of 70°C for 1 hour, then ultrasonically cleaned with deionized water for 5 minutes, and taken out and dried for later use.
[0053] (3) Heat treatment: Place the Al2O3 ceramic substrate obtained in step (2) into a muffle furnace and keep it at 350°C for 3 min;
[0054] (4) Copper ion activation: Place a prepared copper sulfate and vitamin C activation solution with a molar ratio of 1:2 into a modified spray bottle with a volume of 2 L. Take out the Al2O3 ceramic substrate just treated in step (3) from the muffle furnace and activate it within 20 seconds using the modified spray bottle containing the activation solution. The activation time is 10 seconds. After the activation is completed, rinse with deionized water for 20 seconds and then dry for use.
[0055] (5) Preparation of plating solution: 6 g of soluble malate, 9 g of sodium citrate and 8 g of sodium hydroxide were weighed and added into a 1 L beaker. Deionized water was added and stirred to completely dissolve. Then, a mixture of 9 g of copper sulfate and 8 mL of a 37% formaldehyde aqueous solution was slowly added under stirring. Precipitation was initially generated. As stirring occurred, the precipitate gradually dissolved. The solution was then filtered. After filtration, it was poured into a 1 L beaker. 0.02 g of sodium octyl sulfate and 0.004 g of o-phenanthroline were then added. Deionized water was then added to make the beaker solution reach 500 mL to obtain a plating solution.
[0056] (6) Copper plating: The Al2O3 ceramic substrate obtained by the treatment in step (4) is immersed in the plating solution prepared in step (5), and stirred at 40°C for 40 minutes to complete the surface chemical copper plating. The plating bonding strength is tested by the 100-grid method, and the grade is 5B. The square resistance is tested by the four-probe method, and the square resistance is 25mΩ / □.
[0057] Comparative Example 1
[0058] (1) Degreasing: The Al2O3 ceramic substrate with an aluminum oxide content of 97% was immersed in soapy water for ultrasonic cleaning for 15 min, then ultrasonically cleaned with deionized water for 5 min, and then taken out and dried for later use;
[0059] (2) Roughening: The Al2O3 ceramic substrate obtained in step (1) is placed in a roughening solution containing 10% hydrofluoric acid and 2% sulfuric acid at a constant temperature of 70°C for 1 hour, then ultrasonically cleaned with deionized water for 5 minutes, and then taken out and dried for later use;
[0060] (3) Sensitization: The Al2O3 ceramic substrate obtained in step (2) was placed in a SnCl2 sensitization solution for 3 min;
[0061] (4) Activation: The Al2O3 ceramic substrate obtained in step (3) was placed in a PbCl2 activation solution for 1 min, then rinsed with deionized water for 2 s, and taken out and dried for later use;
[0062] (5) Preparation of plating solution: 6 g of soluble malate, 9 g of sodium citrate and 8 g of sodium hydroxide were weighed and added into a 1 L beaker. Deionized water was added and stirred to completely dissolve. Then, a mixture of 9 g of copper sulfate and 8 mL of a 37% formaldehyde aqueous solution was slowly added under stirring. Precipitation was initially generated. As stirring occurred, the precipitate gradually dissolved. The solution was then filtered. After filtration, it was poured into a 1 L beaker. 0.02 g of sodium octyl sulfate and 0.004 g of o-phenanthroline were then added. Deionized water was then added to make the beaker solution reach 500 mL to obtain a plating solution.
[0063] (6) Copper plating: The Al2O3 ceramic substrate obtained by the treatment in step (4) is immersed in the plating solution prepared in step (5), and stirred at 40°C for 40 minutes to complete the surface chemical copper plating. The coating bonding strength is tested by the 100-grid method, and the grade is 5B. The square resistance is tested by the four-probe method, and the square resistance is 35mΩ / □.
[0064] Effect Example 1
[0065] The Al2O3 ceramic electronic substrate copper-plated materials obtained in Examples 1-3 and Comparative Example 1 were tested for bonding strength and square resistance by the hundred-grid method and the four-probe method. The results are summarized in the following table.
[0066] Table 1 Summary of performance tests of various embodiments and comparative examples
[0067]
[0068] Figure 1 This is a comparison of the surface morphology before and after copper activation in Example 1.
[0069] Figure 2 It is a comparison diagram of the surface morphology of comparative example 1 and embodiment 1.
[0070] Depend on Figure 1 It can be seen that after copper activation, sufficient particles are generated and attached to the substrate surface. After EDS characterization, it is confirmed that these particles are copper particles. Figure 2It can be seen that the surface of the copper layer after copper activation is more uniform. It can also be seen from Table 1 that the surface square resistance of the Al2O3 ceramic electronic substrate with a copper layer plated on the surface prepared in each embodiment of the present invention is lower than that prepared by the conventional palladium activation process in Comparative Example 1. In general, the copper layer plated by the method of the present invention is more evenly distributed than the copper layer plated by traditional precious metals, and is firmly bonded to the surface of the material, with a bonding firmness of 5B level, and the cost is extremely low, suitable for large-scale production.
[0071] In summary, the present invention utilizes a muffle furnace to heat the Al2O3 ceramic substrate to an appropriate temperature, and keeps the temperature for an appropriate time, and then utilizes the temperature of the Al2O3 ceramic substrate itself to catalyze the activation liquid uniformly sprayed onto the Al2O3 ceramic substrate to undergo an oxidation-reduction reaction, so that the surface of the Al2O3 ceramic substrate is covered with copper, and then serves as a catalytic center for subsequent chemical copper plating. The present invention overcomes the shortcomings of the previous Al2O3 ceramic electronic substrate palladium activation process, and the copper-plated layer is uniformly distributed, has high production efficiency, is economical and environmentally friendly, and has a simple and easy-to-control process, which is convenient for large-scale production, and has huge potential application prospects.
[0072] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A palladium-free chemical copper plating method suitable for the surface of Al2O3 ceramic electronic substrate, characterized in that: The steps include: Heat treating the Al2O3 ceramic substrate to a specified temperature; Evenly spraying an activation solution on the surface of the Al2O3 ceramic substrate at a specified temperature for activation, wherein the activation solution is a mixed solution of copper sulfate and vitamin C; The activated Al2O3 ceramic substrate is immersed in a plating solution to perform a chemical copper plating reaction.
2. The method according to claim 1, characterized in that The heat treatment is carried out in a muffle furnace, heated to 100° C.-600° C., and kept warm for 1 min-10 min.
3. The method according to claim 1, characterized in that The molar ratio of copper sulfate to vitamin C is 1:1-1:6; And / or, the device used for the activation is a modified spray pot with a volume of 0.5L-5L; And / or, the activation operation occurs within 1s-100s after the Al2O3 ceramic substrate has finished heat treatment; And / or, the activation time is 5s-50s; And / or, the activated Al2O3 ceramic substrate is rinsed with deionized water for 1s-20s and dried.
4. The method according to claim 1, characterized in that The plating solution preparation process is as follows: copper sulfate, soluble malate, sodium citrate, sodium hydroxide, 37% formaldehyde aqueous solution by mass fraction, sodium n-octyl sulfate and o-phenanthroline are added into deionized water and mixed and dissolved.
5. The method according to claim 4, characterized in that The amount of copper sulfate relative to deionized water is 6-26 g / L; And / or, the amount of the soluble malate relative to deionized water is 4-24 g / L; And / or, the amount of sodium citrate relative to deionized water is 5-25 g / L; And / or, the amount of sodium hydroxide used relative to deionized water is 5-25 g / L; And / or, the dosage of the formaldehyde aqueous solution relative to deionized water is 5-50 mL / L; And / or, the amount of sodium n-octyl sulfate relative to deionized water is 0.005-0.05 g / L; And / or, the amount of o-phenanthroline used relative to deionized water is 0.005-0.05 g / L.
6. The method according to claim 1, characterized in that The reaction temperature of the chemical copper plating reaction is 20° C.-70° C.; and / or the reaction time of the chemical copper plating reaction is 10-60 min.
7. The method according to any one of claims 1 to 6, characterized in that: The method further comprises: before the heat treatment, ultrasonically cleaning the Al2O3 ceramic substrate to degrease it, and then roughening it in a roughening liquid; and / or, the Al2O3 ceramic substrate has an Al2O3 content of 90%-99%.
8. The method according to claim 7, characterized in that The ultrasonic cleaning is firstly performed once with soap solution and then performed twice with deionized water.
9. The method according to claim 8, characterized in that The time for the first ultrasonic cleaning is 10-30 minutes; the time for the second ultrasonic cleaning is 1-10 minutes.
10. The method according to claim 7, characterized in that The roughening liquid comprises 2%-20% hydrofluoric acid and 0.5%-5% sulfuric acid, and the roughening conditions are roughening at a temperature of 50° C.-100° C. for 0.5 h-5 h; and / or, ultrasonic cleaning with deionized water for 1-10 min after roughening.